Religious moderation through social pedagogy: Lessons from Sahur Kebangsaan with Sinta Nuriyah Wahid in Islamic higher education - Endang Dwi Pratiwi Ningrum; Arini Eka Azzahra; Isyana Nasywa Aini; Naila Putri Salsabila; Amelianawati; Anggun Fina Rahmadani; Lotus Chairunisa Rajanendri; Risma Fajarini; Dinda Intan Lestari; Arditya Prayogi (PT Perfidia Akademia, 2026)
Religious moderation in Islamic higher education has primarily been examined as an outcome of institutional policies and formal learning, while the pedagogical mechanisms embedded in socio-religious practices remain underexplored. This study aims to analyze the manifestations of religious moderation and conceptualize Sahur Kebangsaan as a model of social pedagogy in Islamic higher education. Using a qualitative document analysis approach, the study examined official institutional documents, speeches by Sinta Nuriyah Wahid, and supporting publications through thematic analysis. The findings reveal that Sahur Kebangsaan embodies four dimensions of religious moderation—national commitment, tolerance, anti-violence, and accommodation of local culture—through spiritual reflection, collective dialogue, shared experience, and community participation. This study contributes by proposing a conceptual model of Sahur Kebangsaan as social pedagogy, demonstrating how religious rituals can be transformed into pedagogical mechanisms that foster an inclusive campus culture and strengthen religious moderation. Abstrak Moderasi beragama di pendidikan tinggi Islam masih lebih banyak dikaji sebagai hasil kebijakan atau pembelajaran formal, sementara mekanisme pembentukannya melalui praktik sosial-keagamaan masih relatif terbatas. Penelitian ini bertujuan menganalisis manifestasi moderasi beragama serta mengonseptualisasikan Sahur Kebangsaan sebagai social pedagogy dalam pendidikan tinggi Islam. Penelitian menggunakan pendekatan analisis dokumen kualitatif dengan sumber data berupa dokumentasi resmi UIN K.H. Abdurrahman Wahid Pekalongan, pidato Sinta Nuriyah Wahid, dan publikasi pendukung yang dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa Sahur Kebangsaan memanifestasikan empat indikator moderasi beragama, yaitu komitmen kebangsaan, toleransi, anti-kekerasan, dan akomodatif terhadap budaya lokal melalui refleksi spiritual, dialog kolektif, pengalaman bersama, dan partisipasi masyarakat. Penelitian ini berkontribusi dengan menawarkan model konseptual Sahur Kebangsaan sebagai social pedagogy yang menjelaskan bagaimana ritual keagamaan dapat bertransformasi menjadi mekanisme pedagogis dalam membangun budaya kampus yang inklusif dan memperkuat moderasi beragama.